2023
DOI: 10.5005/jp-journals-11002-0058
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Memory in Macrophages

Abstract: Macrophages have been recognized as the primary mediators of innate immunity starting from embryonic/fetal development. Macrophagemediated defenses may not be as antigen-specific as adaptive immunity, but increasing information suggests that these responses do strengthen with repeated immunological triggers. The concept of innate memory in macrophages has been described as "trained immunity" or "innate immune memory (IIM). " As currently understood, this cellular memory is rooted in epigenetic and metabolic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 325 publications
0
4
0
Order By: Relevance
“…TLR family members are crucial in identifying infiltrating microbiota and in reprogramming innate immunity 20,21 . LPS is the main component of the Gram‐negative bacteria cell wall, which could be recognized by TLR4 expressed on various cell types to activate inflammatory cytokine expression 22,23 . The signaling transduction of LPS‐TLR4 is mediated through the Myd88 pathway, and this transduction finally results in inflammatory cytokine expression 24,25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TLR family members are crucial in identifying infiltrating microbiota and in reprogramming innate immunity 20,21 . LPS is the main component of the Gram‐negative bacteria cell wall, which could be recognized by TLR4 expressed on various cell types to activate inflammatory cytokine expression 22,23 . The signaling transduction of LPS‐TLR4 is mediated through the Myd88 pathway, and this transduction finally results in inflammatory cytokine expression 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 21 LPS is the main component of the Gram‐negative bacteria cell wall, which could be recognized by TLR4 expressed on various cell types to activate inflammatory cytokine expression. 22 , 23 The signaling transduction of LPS‐TLR4 is mediated through the Myd88 pathway, and this transduction finally results in inflammatory cytokine expression. 24 , 25 Zhang and colleagues report that in LPS‐stimulated RAW264.7 cells, NAC‐S2 treatment significantly suppresses TNF‐α and IFN‐γ production.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of candidate vaccines is still in an early phase. 56 There are two extensive reviews focused on macrophages 57 and mitochondria, 58 respectively. In fetuses, neonates, and young infants, macrophages serve a very important role in immune defenses.…”
Section: Editorialmentioning
confidence: 99%
“…To date, extensive studies have revealed various epigenetic modifications, such as histone modifications, DNA methylation, and non-coding RNA expression, that determine macrophage states [10,13]. Among them, histone modifications, particularly in H3K4 mono-or tri-methylation (H3K4me1/3) and H3K27 acetylation (H3K27ac), are transactivating markers that are involved in training/priming, whereas H3K9 di/tri-methylations (H3K9me2/3) are repressive markers of tolerated genes [14][15][16].…”
Section: Introductionmentioning
confidence: 99%